Response of humpback whales (Megaptera novaeangliae) to ramp-up of a small experimental air gun array. Issue 1 (15th February 2016) - Dunlop, Rebecca A.; Noad, Michael J.; McCauley, Robert D.; Kniest, Eric; Slade, Robert; Paton, David; Cato, Douglas H.
Abstract: 'Ramp-up', or 'soft start', is a mitigation measure used in seismic surveys and involves increasing the radiated sound level over 20–40 min. This study compared the behavioural response in migrating humpback whales to the first stages of ramp-up with the response to a 'constant' source, 'controls' (in which the array was towed but not operated) with groups in the absence of the source vessel used as the 'baseline'. Although the behavioural response, in most groups, resulted in an increase in distance from the source (potential avoidance), there was no evidence that either 'ramp-up' or the constant source at a higher level was superior for triggering whales to move away from the source vessel. 'Control' groups also responded suggesting the presence of the source vessel had some effect. However, the majority of groups appeared to avoid the source vessel at distances greater than the radius of most mitigation zones. Highlights: Humpback whales are likely to move away from a source during a ramp-up sequence. Starting at a higher initial level was no better at triggering whales to move away. Using a ramp-up procedure would limit acoustic exposure while close to the source.